4-H Swine Project Manual Book 1 - Kenneth L. Durrance; Cynthia A. Maxson; Nancy Johnson (EDIS)
This document is 4HSWM10 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Printed; December, 1990, Reviewed June 2002.